AIRI AS AN ADAPTIVE FRAMEWORK LINKING DIGITAL EDUCATION MANAGEMENT TO HOLISTIC INDUSTRY 4.0 READINESS - Amin, Syaiful; Situngkir, Budi Argap; Pramono, Suwito Eko; Arifin, Ridwan (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
As schools rapidly adopt Education Management Information Systems (EMIS), data-driven decision-making, and technology-enhanced instruction, there is growing interest in understanding how digital education management shapes students’ readiness for Industry 4.0. This study aims to clarify the systemic role of digitalization in developing students’ cognitive, digital, and socio-adaptive competencies by proposing a comprehensive evaluation framework. A qualitative, theory-driven design was employed, synthesizing literature on digital education management, evaluation models, and readiness theory. The study developed the Adaptive-Integrated Readiness Index (AIRI), integrating concepts from CIPP, TPACK, and existing digital readiness indices to assess the combined influence of infrastructure, managerial processes, technological integration, instructional innovation, and institutional policies on multidimensional student readiness. Analysis indicates that current digitalization initiatives are fragmented and that prevailing evaluation approaches often focus narrowly on technology tools or user acceptance. AIRI demonstrates that students’ readiness is best understood as a dynamic capability shaped by interconnected digital management processes rather than isolated interventions. By reconceptualizing readiness as an emergent property of integrated digital management, AIRI provides policymakers and practitioners with a diagnostic framework to assess the impact of digital initiatives, identify areas for improvement, and align technology investments with Industry 4.0–oriented learning outcomes. The study highlights the importance of systemic evaluation to ensure that digitalization efforts translate into meaningful, holistic student competencies.